2020
DOI: 10.1111/ejss.12996
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte infection influences arbuscular mycorrhizal fungi communities in rhizosphere soils of host as opposed to non‐host grass

Abstract: Endophytes live asymptomatically within many cool‐season grasses for at least a portion of their life cycle. Although the leaf endophyte effects on the growth and stress resistance of host grasses have been relatively well studied, less attention has been focused on how this relationship may impact soil microbial communities, especially arbuscular mycorrhizal fungi (AMF). We defined endophyte‐infected and endophyte‐free Leymus chinensis as the host grass and neighbouring Stipa krylovii, which was not infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…However, there are relatively few reports on the effects of Epichloë endophytes on microbial communities, and research results are inconsistent. One study suggested that Epichloë endophytes can affect the microbial diversity in the roots and rhizosphere (Liu et al, 2021 ). Another study has reported that E. festucae var.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are relatively few reports on the effects of Epichloë endophytes on microbial communities, and research results are inconsistent. One study suggested that Epichloë endophytes can affect the microbial diversity in the roots and rhizosphere (Liu et al, 2021 ). Another study has reported that E. festucae var.…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë endophytes can affect nutrient cycling and alter soil physicochemical properties (Guo et al, 2016). Extensive studies have shown that changes in soil nutrients can alter the diversity and composition of microbial communities in plant root systems and soil (Liu et al, 2015(Liu et al, , 2020. The effect of Epichloë endophytes of grasses on soil chemistry and microbial community varies depending on host species, endophyte genetics, soil type and experimental treatments (Casas et al, 2011;Jenkins et al, 2006;Larimer et al, 2012;Rojas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These root-associated microorganisms promote plant growth through root-hair proliferation, enhancing soil fertility; increase in nitrogen fixation ability; enhanced leaf surface area; improvement in vigor and biomass; increased indigenous plant hormones levels; and most importantly, by improving nutrient use efficiency (Fan et al, 2020;Singh R. K. et al, 2022). The most studied microorganisms that are affected by the Epichloë endophytes are AMF, and the results have shown that Epichloë endophytes can change the colonization, diversity and community of AMF (Vignale et al, 2016;Liu et al, 2020Liu et al, , 2022aTerlizzi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the grass- Epichloë endophytes symbiotic relationship, the grass provides the endophytes with nutrients and shelter, and in exchange, the endophytes promote grass growth and confer protection against abiotic such as drought and saline-alkali and biotic such as herbivores and foliar pathogens stressors ( Chen et al, 2017 ; Liu et al, 2017 , 2022a ; Qin et al, 2019 ; Li et al, 2020 ; Yang et al, 2020 ). Although the consequences of Epichloë endophyte infection on the growth and resistance of host grasses have been well documented, to our knowledge, only a few papers have measured the impact of aboveground Epichloë endophytes on belowground components, especially on microorganisms ( Arrieta et al, 2015 ; Vignale et al, 2016 ; Zhong et al, 2018 ; Liu et al, 2020 , 2022b ; Mahmud K. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation